2019
DOI: 10.1016/j.heliyon.2019.e02472
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of perfluoroalkyl substances in selected Victorian rivers and estuaries: An historical snapshot

Abstract: This reconnaissance study was undertaken in 2012 to examine the occurrence of common perfluoroalkyl substances (PFAS), including perfluoroalkyl sulphonic acids and perfluoroalkyl carboxylic acids in rivers and estuaries in Port Philip Bay, Victoria, Australia. In total, 19 PFAS were screened in grab samples of water using a combination of solid phase extraction and liquid chromatography-mass spectrometry measurement techniques. Eighteen of the PFAS screened were observed in samples. The highest level of PFOS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 67 publications
(63 reference statements)
3
8
0
Order By: Relevance
“…Seven long-chain PFCA (perfluorodecanoic acid [PFDA], perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorotetradecanoic acid, perfluorohexadecanoic acid, perfluorooctadecanoic acid, and 8:2 fluorotelomer unsaturated carboxylic acid), 3 PFSA (perfluoroheptane sulfonic acid, perfluorononane sulfonic acid, and perfluorodecane sulfonic acid), and 8 fluorotelomer-based PFAS compounds (N-methyl perfluorooctane sulfonamide, N-ethyl perfluorooctane sulfonamide, N-ethyl perfluorooctane sulfonamidoacetic acid, N-methyl perfluorooctane sulfonamidoethanol [N-MeFOSE], N-ethyl perfluorooctane sulfonamidoacetic acid [N-EtFOSAA], N-ethyl perfluorooctane sulfonamidoethanol [N-EtFOSE], 4:2 fluorotelomer sulfonic acid [FTS], and 6:2 FTS) were not detected in any of the 3 abiotic matrices (see LORs in Table 2). The PFAS found in water samples in the present study aligns with previous investigations in Victoria (Szabo et al 2018;Allinson et al 2019;Sardiña et al 2019), although differences attributable to land use were apparent. Sardiña et al (2019) reported a similar suite of PFAS in water collected from rivers and wetlands surrounded by agricultural land, which is also the dominant land-use type in the catchments of most of the wetlands analyzed in the present study.…”
Section: Pfas In Water Sediment and Soilsupporting
confidence: 91%
See 1 more Smart Citation
“…Seven long-chain PFCA (perfluorodecanoic acid [PFDA], perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorotetradecanoic acid, perfluorohexadecanoic acid, perfluorooctadecanoic acid, and 8:2 fluorotelomer unsaturated carboxylic acid), 3 PFSA (perfluoroheptane sulfonic acid, perfluorononane sulfonic acid, and perfluorodecane sulfonic acid), and 8 fluorotelomer-based PFAS compounds (N-methyl perfluorooctane sulfonamide, N-ethyl perfluorooctane sulfonamide, N-ethyl perfluorooctane sulfonamidoacetic acid, N-methyl perfluorooctane sulfonamidoethanol [N-MeFOSE], N-ethyl perfluorooctane sulfonamidoacetic acid [N-EtFOSAA], N-ethyl perfluorooctane sulfonamidoethanol [N-EtFOSE], 4:2 fluorotelomer sulfonic acid [FTS], and 6:2 FTS) were not detected in any of the 3 abiotic matrices (see LORs in Table 2). The PFAS found in water samples in the present study aligns with previous investigations in Victoria (Szabo et al 2018;Allinson et al 2019;Sardiña et al 2019), although differences attributable to land use were apparent. Sardiña et al (2019) reported a similar suite of PFAS in water collected from rivers and wetlands surrounded by agricultural land, which is also the dominant land-use type in the catchments of most of the wetlands analyzed in the present study.…”
Section: Pfas In Water Sediment and Soilsupporting
confidence: 91%
“…A recent study in Victoria, southeast Australia, identified industrial and some urban environments as having elevated concentrations of PFAS (Sardiña et al 2019). Another survey of 7 Melbourne waterways and 2 estuaries detected 17 out of 19 measured PFAS in suburban Australian waterways, with the highest PFOS concentrations in the 2 estuaries downstream of heavily industrialized catchments in Melbourne's western suburbs (Allinson et al 2019). Fewer studies have attempted to understand the relationship between PFAS concentrations in the environment and those in biota (but see Taniyasu et al 2003; Bossi et al 2005; Thompson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PFOA had the highest mean concentration in water (47 ± 3.1 ng L –1 ), followed by PFOS (31 ± 9.6 ng L –1 ) and PFHxS (12 ± 0.56 ng L –1 ). The mean concentrations of PFOA, PFOS, and PFHxS in this study exceed the concentrations found in the catchment from the closest major waterway (∼1.5 km), where concentrations were 1.7–2.2 ng L –1 , 5.1–13.9 ng L –1 , and 3.0–7.0 ng L –1 , respectively . Furthermore, average concentrations of PFOS exceed the Australian guideline for 99% species conservation (0.23 ng L –1 ) and the maximum concentration of PFOS (151 ng L –1 ) exceeded the 95% species conservation guideline of 130 ng L –1 51 .…”
Section: Resultsmentioning
confidence: 88%
“…These samples contained the highest PFAS concentrations, with a maximum detected of 424 ng L −1 for PFPeA, followed by PFOA (approx 200 ng L −1 ), similarly to other studies carried out in surface waters, where PFAS levels have been found in the low ng L −1 range in rivers of urban catchments. 31–33 In seawater samples, 7 compounds were detected, but only 3 were above MQLs. The highest concentrations were around 45 and 13 ng L −1 for the compounds PFBS and PFPeA, respectively, an order of magnitude lower than in river water, comparable to similar studies in ocean water.…”
Section: Resultsmentioning
confidence: 99%